2019
DOI: 10.3389/fendo.2019.00356
|View full text |Cite
|
Sign up to set email alerts
|

Differential Apoptotic and Mitogenic Effects of Lectins in Zebrafish

Abstract: Plant lectins represent a major group of anti-nutritional factors that can be toxic to human and animals. However, the mechanisms by which lectins regulate cell fates are not well-understood. In the present study, the cellular and molecular impacts of three common lectins, agglutinins from wheat germ [wheat germ agglutinin (WGA)], soybean [soybean agglutinin (SBA)], and peanut [peanut agglutinin (PNA)] were examined in zebrafish embryo and liver cells. WGA and SBA were found to induce cell apoptosis both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
0
4
0
1
Order By: Relevance
“…Lectins (LEC) are used as natural plant insecticides. When consumed by people, they trigger immune responses in people depending on the dose [ 56 , 57 , 58 , 59 , 60 , 61 ]. Lectins are present in abundant amounts in soybeans, red kidney beans, red hot peppers, potatoes, tomatoes, wheat germ, eggplant, nuts, raw unpasteurized milk, and mother’s breast milk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lectins (LEC) are used as natural plant insecticides. When consumed by people, they trigger immune responses in people depending on the dose [ 56 , 57 , 58 , 59 , 60 , 61 ]. Lectins are present in abundant amounts in soybeans, red kidney beans, red hot peppers, potatoes, tomatoes, wheat germ, eggplant, nuts, raw unpasteurized milk, and mother’s breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…Most lectins are relatively heat-resistant to temperatures up to 70° C and rigorous heating conditions are required for their inactivation. Lectins present in soybeans, wheat grains (1 wheat grain has 10 μg of lectin), peppers, milk, and tomatoes are routinely consumed by people worldwide [ 56 , 57 , 58 , 59 , 60 , 61 ]. Our study has shown that LEC10 and LEC50 robustly induced gene expression of PSMB8 (LMP7), and most inflammatory cytokines like LPS (a potent prototype and proinflammatory agonist, which induces both innate and acquired immunity) as described below ( Figure 5 A–D).…”
Section: Discussionmentioning
confidence: 99%
“…The biological significance of the isolated lectins in various marine organisms has not been fully elucidated, and investigations are currently ongoing [ 14 ]. Nevertheless, their roles in aquatic animals (i.e., reproduction, defense against pathogenic microbes (immunity), polyspermy block, morphogenesis and embryogenesis) are well studied [ 15 , 16 , 17 ]. The major classes of lectins identified in marine animals are C-type lectins (CTLs), F-type lectins (FTLs), X-type lectins (XTL), galectins (formerly S-type lectins), and pentraxins (P-type lectins) [ 6 , 18 ].…”
Section: Marine Organism-derived Lectinsmentioning
confidence: 99%
“…The applied polymers were hardly suited for pharmaceutical use (non-biodegradable Sepharose). Furthermore, ConA is notoriously toxic (mitogenic) [ 36 , 37 ], so ConA is not relevant for drug use. Although PEGylation of ConA was later pursued, this approach will not mitigate the issue of toxicity [ 38 ].…”
Section: Polymer-based Conceptsmentioning
confidence: 99%